Nutrition knowledge, attitudes and dietary practices of University of the Philippines athletes - De Los Santos, Leah Teresa F.; Palacpac Jr., Orlino (2007)
A study among selected U.P athletes was conducted to asses their nutrition knowledge, attitudes ad dietary practices. Data were collected through a four-part questionnaire formulated specifically for this study. Part one was about personal information aimed at gathering variables such as sex, college, year level, sport/team, number of training days per week and training attendance. Part two tackled the athlete's level of nutrition knowledge aimed at assessing their knowledge on basic sports nutrition. Part four is a 24-hour food diary aimed at describing their dietary practices when they aimed at describing their dietary practices when they have training and when they do not have training. Statistical test used for data analysis is frequency distribution. In the assessment of the athletes' personal food practices, better attitudes were shown towards alcohol consumption and cigarette smoking. Th water intake of athletes showed poor practice. For the nutrition knowledge test, the statement that was answered correctly by the biggest number of respondents was "Dehydration decreases performance". The statements that were incorrectly answered by the biggest number of respondents are "Athletes should drink every 30 minutes during training or competition," and "Eating candies and sweets during training/competition delay fatigue. The respondents faired "Highly satisfactory" in the nutrition knowledge test. The dietary practices of these selected athlete eat a rice, meat and vegetable dish accompanied with water for all major meals - breakfast, lunch and dinner. Majority do not eat snack particularly midnight snacks.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Athletes -- Nutrition -- Philippines